Advance cryptography algorithm for improving data security - SINGH, YASHWANT KUMAR; Milan, Ram; RATAWA, SURYA PRAKASH (IJRDO -Journal of Computer Science Engineering, 2017)
Information security is the process of protecting information. It protects its availability, privacyand integrity. Access to stored information on computer databases has increased greatly. Morecompanies store business and individual information on computer than ever before. Much of theinformation stored is highly confidential and not for public viewing. In this paper, I have developed a newcryptography algorithm, which is based on block cipher concept. In this algorithm, I have used logicaloperation like XOR and shifting operation. Experimental results show that proposed algorithm is veryefficient and secured.To write this paper I have Study about information security using cryptography technique. After thedetailed study of Network security using cryptography, I am presenting my proposed work. This paper isdividing in four sections. In section-I, I am presenting just basic introduction about Information Securityusing cryptography, in section-II, I am presenting detailed description of Information security usingcryptography and various algorithms, in section-III, I am presenting my proposed algorithm, and in sectionIV I am Presenting summary and references where I have completed my research. The proposed algorithmhas the batter speed compared with the comparing encryption algorithm. Nevertheless, the proposedalgorithm improves encryption security by inserting the symmetric layer. The proposed algorithm will beuseful to the applications, which require the same procedure of encryption and decryption.